Straight OUTTA Detroit: Embracing Stigma as Part of the Entrepreneurial Narrative. (11th June 2022) - Cowden, Birton J.; Bendickson, Joshua S.; Mathias, Blake D.; Solomon, Shelby J.
Abstract: Through an inductive field study, we set out to better understand how and why ventures would embrace a non‐core stigma; this is perplexing given that a majority of stigma literature suggests that organizations tend to avoid/disidentify from stigmatized entities. To do so, we study organizational locational stigma, which we define as a label arising from an organization's geographic location that evokes a collective stakeholder group‐specific perception that an organization possesses a fundamental, deep‐seated flaw that deindividuates and discredits the organization . Our findings from Detroit, Michigan reveal that entrepreneurs embrace the locational stigma by taking part in Detroit's underdog narrative and comeback story . Entrepreneurs use the underdog narrative in hope of differentiating their ventures from those in other locations, while they leverage the comeback story to gain access to the resources and in‐group advantages. We thus advance the concept of locational stigma and show how it can benefit organizations.